The Effect of Financial Literacy and Electronic Money on Consumptive Behavior With Self-Control as Mediation: The Effect of Financial Literacy and Electronic Money on Consumptive Behavior With Self-Control as Mediation - Shintya, Neha; Sutrisno; Meiriyanti, Rita (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the influence between financial literacy and electronic money on consumptive behavior both directly and through self-control in students mediated by self-control. This study applies a quantitative method with primary data obtained from questionnaire data which is then processed using SmartPLS 3.0 software. The sample in this study was 314 students. The sampling technique used is a simple random sampling technique. The results of this study show that financial literacy does not have a significant effect on consumptive behavior, electronic money has a significant positive effect on consumptive behavior, financial literacy and electronic money has a significant positive effect on self-control, self-control has a significant positive effect on consumptive behavior. Then self-control is able to mediate the influence of financial literacy on consumptive behavior, and self-control is unable to mediate the influence of electronic money on the consumptive behavior of FEB students PGRI University of Semarang.